Prevalence of Oral Allergy Syndrome among Adults with Prevalence and Linkages with Various Factors - Sadaf Raffat Mustafa, Syed Nadeem Ul Haq, Wajih-Ud-Din Shinwari, Farhan Ahmed Bhatti, Muhammad Jamil, Muhammad Osama (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Oral allergy syndrome is the most common manifestation of food allergies in adults. However, population-based studies assessing its prevalence and associated factors remain limited in Pakistan. Objective: To determine the prevalence of oral allergy syndrome among university students and to describe its clinical characteristics and associated factors. Study Design: Cross sectional, survey-based study. Place and Duration of Study: Department of ENT, Hitec Institute of Medical Sciences, Taxilla Cantt from 1st January 2023 to 30th June 2023. Methodology: One thousand and two hundred patients within 18-35 years of age who walked in the outdoor patient of ENT were enrolled. Out of which oral allergy syndrome was found in 100 cases through clinical diagnostic tests including spirometry and clinical proforma. Each participant was informed through a written consent form of the study background and objectives. A complete nasal examination was conducted before specifying allergic rhinitis cases within total enrolled participants. Each participant was given a well structured proforma (asthma, allergic- rhinitis, and atopic dermatitis), pollen/latex, food allergy. The oral and the extraoral symptoms associated were also documented. Results: 8.3% cases having oral allergic syndrome. There were 42 males and 58 females with almost no significant variance in the mean ages of the participants in accordance with their gender and 10% vs 6% cases of asthma of males and females respectively. There was a significant variance among patients suffering from allergic rhinitis, while pollen allergy was observed almost similarly among males and females. The associated factors with oral allergies were observed in detail among all the patients. Lip pruritic was observed in 90% of the oral allergy cases followed by lip edema and pharyngeal oppression in 56% and 27% cases respectively. Additionally, among the various associated food items causing oral allergy the highest prevalence of fruit related (69%) allergies. Conclusions: The prevalence of oral allergy syndrome varies by geographic region. A personal history of pollen or latex allergy was identified as a key risk factor for oral allergy syndrome in this population. Keywords: Food allergies, Oral allergy syndrome, Prevalence, Pollen food syndrome